Board Of Director's Networks And Earnings Quality In Malaysia - Jamaludin, Mohd Faizal (2017)
Malaysia critically suffered from the world financial crisis in 1997, which significantly effects the capital market of all Asian region countries. The financial crisis in emerging market like Malaysia revealed the critical need for firm to enhance corporate governance mechanism. The board of director characteristics is part of corporate governance mechanism, which has been major focus to strengthen firm’s corporate governance, thus restore the investor’s confidence towards a sustainable Malaysian capital market. Prior empirical had shown that one of the board of director’s characteristics is identified as key component affecting the earnings quality.